INVESTIGATION OF THE N-TERMINAL CODING REGION OF MUC7 ALTERATIONS IN DENTISTRY STUDENTS WITH AND WITHOUT CARIES - YARAT, AYŞEN; AKYÜZ, SERAP HATİCE (MACEDONIAN ACAD SCIENCES ARTS, 2016)
Human low-molecular weight salivary mucin (MUC7) is a small, secreted glycoprotein coded by MUC7. In the oral cavity, they inhibit the colonization of oral bacteria, including cariogenic ones, by masking their surface adhesions, thus helping saliva to avoid dental caries. The N-terminal domain is important for low-molecular weight (MG2) mucins to contact with oral microorganisms. In this study, we aimed to identify the N-terminal coding region of the MUC7 gene between individuals with and without caries. Forty-four healthy dental students were enrolled in this study; 24 of them were classified to have caries [decayed, missing, filled-teeth (DMFT) = 5.6] according to the World Health Organization (WHO) criteria, and 20 of them were caries-free (DMFT = 0). Simplified oral hygiene index (OHI-S) and gingival index (GI) were used to determine the oral hygiene and gingival conditions. Total protein levels and salivary total protein levels and salivary buffer capacity (SBC) were determined by Lowry and Ericsson methods. DNA was extracted from peripheral blood cells of all the participants and genotyping was carried out by a polymerase chain reaction (PCR)-sequencing method. No statistical differences were found between two groups in the terms of salivary parameters, oral hygiene and gingival conditions. We detected one common single nucleotide polymorphism (SNP) that leads to a change of asparagine to lysine at codon 80. This substitution was found in 29.0 and 40.0%, respectively, of the groups with and without caries. No other sequence variations were detected. The SNP found in this study may be a specific polymorphism affecting the Turkish population. Further studies with extended numbers are necessary in order to clarify this finding.
Keywords: Dental caries; oral hygine indicis; low molecular weight salivar mucin (MUC7); SALIVARY MUCIN; CANDIDACIDAL ACTIVITY; STREPTOCOCCUS-MUTANS; PEPTIDES; DOMAIN